Diffuse idiopathic skeletal hyperostosis of the spine in a nine‐year‐old cat. (26th May 2015) - Bossens, K.; Bhatti, S.; Van Soens, I.; Gielen, I.; Van Ham, L.
Abstract : A nine‐year‐old intact female domestic shorthair cat was evaluated for paraparesis, ataxia and severe spinal hyperaesthesia. Neurological examination indicated a T3‐L3 spinal cord segment lesion. Computed tomography of the thoracolumbar and lumbosacral vertebral column was performed. This showed contiguous smooth new bone formation ventral and lateral to the vertebrae extending from the cranial thoracic area to the lumbosacral junction and appearing similar to canine diffuse idiopathic skeletal hyperostosis. There was also marked dorsolateral stenosis of the vertebral canal at the level of T4‐T5 because of degenerative changes of the facet joints. To the authors' knowledge, this is the first published report of feline diffuse idiopathic skeletal hyperostosis.